PRIVATE AND PUBLIC PENSION SYSTEMS WORLWIDE: CASE OF RUSSIA - A. V. Pudovkin (Vestnik MGIMO-Universiteta)
The article deals with the Russian pension system and make recommendations for its further development on the basis of international experience. The Russian pension system is in a state of transition. The reform of 2013-2015 is not completed, since in its current state pension system is still characterized by very low replacement rate value at a very high level of government spending. Moratorium on pension accumulation introduced in the course of recent reforms calls into question the future of the mandatory funded pension system. Review of international pension systems formation suggests that the most successful of them are not limited solely to public system, and use a combination of distribution and accumulation units. When choosing between mandatory or voluntary options they are guided by the characteristics of the national economy. Studying the successes and mistakes of world practice of voluntary and mandatory funded pension systems is of great scientific and practical interest, since it can contribute to a more accurate choice of the future path of development of the national pension system.